2014
DOI: 10.1242/jcs.165761
|View full text |Cite
|
Sign up to set email alerts
|

Syndecan defines precise spindle orientation by modulating Wnt signaling in C. elegans

Abstract: Wnt signals orient mitotic spindles in development, but it remains unclear how Wnt signaling is spatially controlled to achieve precise spindle orientation. Here, we show that C. elegans syndecan (SDN-1) is required for precise orientation of a mitotic spindle in response to a Wnt cue. We find that SDN-1 is the predominant heparan sulfate (HS) proteoglycan in the early C. elegans embryo, and that loss of HS biosynthesis or of the SDN-1 core protein results in misorientation of the spindle of the ABar blastomer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…Alternatively, it is also possible that the gradient-independent or contact-dependent processes require transmembrane co-factors that mediate contact-dependent Wnt signaling. sdn-1/syndecan was one such candidate as it has been shown that sdn-1 is required for the Wnt-dependent spindle orientation in early embryonic development (Dejima et al, 2014), and sdn-1 mutants exhibit PDB structure defects similar to lin-44/wnt (Saied-Santiago et al, 2017). However, we did not observe significant pruning defects in PDB of sdn-1 mutants (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, it is also possible that the gradient-independent or contact-dependent processes require transmembrane co-factors that mediate contact-dependent Wnt signaling. sdn-1/syndecan was one such candidate as it has been shown that sdn-1 is required for the Wnt-dependent spindle orientation in early embryonic development (Dejima et al, 2014), and sdn-1 mutants exhibit PDB structure defects similar to lin-44/wnt (Saied-Santiago et al, 2017). However, we did not observe significant pruning defects in PDB of sdn-1 mutants (data not shown).…”
Section: Discussionmentioning
confidence: 99%